Nordisk barnelitteratur ̶ et nytt kunstforskningsspørsmål? - Kristin Ørjasæter (Barnboken: Tidskrift för Barnlitteraturforskning, 2013)
Note: This article is being published simultaneously in Nordic ChildLit Aesthetics/Barnelitterært forskningstidsskrift and  Barnboken – tidskrift för barnlitteraturforskning/Journal of Children’s Literature Research.